LGBQ+ adults' experiences of Improving Access to Psychological Therapies and primary care counselling services: informing clinical practice and service delivery. (2019) - Foy, Amelia A.J.; Morris, Daniel; Fernandes, Vanessa; Rimes, Katharine A.
Abstract: Lesbian, gay, bisexual, queer and other sexual minority (LGBQ+) people experience higher levels of psychological difficulties than heterosexual people. Evidence suggests that LGBQ+ treatment outcomes within England's Improving Access to Psychological Therapies (IAPT) services are worse than the outcomes for heterosexuals, especially for bisexual people and sexual minority women. IAPT services provide evidence-based treatments like cognitive behavioural therapy (CBT), typically for anxiety or depression. This study explored LGBQ+ adults' experiences with IAPT services and/or primary care counselling. LGBQ+ adults ( n = 136) answered an online questionnaire (fixed-response and optional open-ended questions) about their access and treatment experiences. Descriptive statistics summarized multiple-choice responses. Qualitative data were analysed through thematic analysis. Before access, 41.9% of participants were concerned about experiencing LGBQ+ stigma/discrimination within psychological services. Only 13.2% of participants thought their sexuality negatively impacted their treatment, although prejudice/discrimination may be underestimated as 33.6% participants did not disclose their sexuality to practitioners and sexuality was not discussed in treatment for 44.0% of participants. Bisexual clients were significantly less likely to disclose their sexuality. The barriers LGBQ+ people described within IAPT or primary care services included: feared or experienced stigma in the services; reluctance to disclose sexuality; inconsistent discussion of sexuality in treatment; a lack of awareness and understanding towards LGBQ+ identities and community-specific challenges; and distrust, disillusionment and exclusion resultantly. Overall, 52.2% thought services could be improved for LGBQ+ individuals. This study identified multiple issues to be addressed in therapist training and service development. Key learning aims: (1) The unique needs/experiences that LGBQ+ people bring to therapy, such as the need to disclose their sexuality and past experiences of stigma/discrimination, including how this differs within the community (e.g. bisexual people or LGBQ+ Black and minority ethnic people). (2) How these needs/experiences can result in barriers that make their treatment experience distinct from heterosexuals and influence their treatment outcomes. (3) What steps should be taken in future research and clinical practice to ensure improvements in the psychological treatment experiences of LGBQ+ people, including in relation to therapist understanding and training in LGBQ+-related issues.